2019
DOI: 10.3390/molecules24020326
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Depressive Effectiveness of Baicalin In Vitro and In Vivo

Abstract: Baicalin (BA), a major polyphenol compound isolated from the extracts of Scutellaria radix, has been previously reported to ameliorate depressive-like behaviors in mice with chronic unpredictable mild stress (CUMS). However, its underlying antidepressant mechanisms remain unclear. This study was designed to confirm the antidepressant-like effects of BA on CUMS induced behavioral abnormalities in mice, and sought to explore the pharmacological mechanisms in vivo and in vitro. The CUMS procedure was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 38 publications
2
70
0
Order By: Relevance
“…Baicalin, one of the main active ingredients of the traditional Chinese medicine drug Scutellaria radix, was investigated for its antidepressive effects in mice with chronic unpredictable mild stress [112]. Baicalin treatment showed antidepressant effects and considerably inhibited proinflammatory cytokine levels, including IL-6.…”
Section: Natural Productsmentioning
confidence: 99%
“…Baicalin, one of the main active ingredients of the traditional Chinese medicine drug Scutellaria radix, was investigated for its antidepressive effects in mice with chronic unpredictable mild stress [112]. Baicalin treatment showed antidepressant effects and considerably inhibited proinflammatory cytokine levels, including IL-6.…”
Section: Natural Productsmentioning
confidence: 99%
“…Baicalin can penetrate BBB, has strong biological activity, and has been widely used in the clinical treatment of infectious and inflammatory disorders [82]. Preclinical studies have shown that baicalin exhibits antidepressant effects by inhibiting the GSK3β/ NF-κB/NLRP3 signaling pathway and downregulating overactivated HPA axis [83][84][85][86][87]. Moreover, baicalin can mitigate obesity and insulin resistance during diabetes treatment by activating the AKT/AS160/GLUT4 pathway and increasing the insulin sensitivity of lipocytes [88,89].…”
Section: Thoughts On Baicalin In the Treatment Of Ddmentioning
confidence: 99%
“…In mice models of chronic (unrestraint) mild stress (CUMS), baicalin (25, 50 and 60 mg/kg) alleviates depression-like behavior by increasing sucrose consumption and reducing immobility times in the tail suspension and forced swim tests [138][139][140]. These effects are associated with a reduction of inflammatory cytokines IL-1β, IL-6, and TNF-α levels in serum and in the hippocampus [138,139]. In mice subjected to CUMS baicalin also abrogates the increase in NMDAR/NR2B and Ca2+/calmodulin-dependent protein kinase II (CaMPK-II) as well as the decrease in pERK, while counteracting reactive oxygen species (ROS) production [138].…”
Section: Chronic (Unrestraint) Mild Stress-induced Depressionmentioning
confidence: 99%
“…In mice subjected to CUMS baicalin also abrogates the increase in NMDAR/NR2B and Ca2+/calmodulin-dependent protein kinase II (CaMPK-II) as well as the decrease in pERK, while counteracting reactive oxygen species (ROS) production [138]. Baicalin administration also counteracts CUMS-and neuroinflammation (LPS)-induced depressive-like behavior in mice, and this occurs through downregulation of TLR4 via the HMBG1/NF-kb [139] and PI3K/AKT/FoxO1 pathways [140].…”
Section: Chronic (Unrestraint) Mild Stress-induced Depressionmentioning
confidence: 99%
See 1 more Smart Citation